Managing Projects in an Uncertain and Volatile World: Engaging Stakeholders, and Building a Systemic View of Risk - Ackermann, Fran; Howick, S.; Quigley, J.; Walls, L.; Houghton, T. (ANZAM, 2012)
As evidenced through both a historical and contemporary number of over-runs managing projects can be a risky business. Managers are faced with effectively working with a multitude of parties, dealing with a wealth of interlocking uncertainties and frequently undertaking these activities within a compressed timeframe. This paper describes a risk management process developed to assist managers facing such situations. The process explicitly engages a range of stakeholders using a group support system and causal mapping process and provides not only a comprehensive appreciation of the risks identified but also a greater understanding of their subtleties. Using a real case the paper will describe the process and outcomes along with its implications, before reflecting on the insights, limitations and future research.